miRNAS in cardiovascular diseases: potential biomarkers, therapeutic targets and challenges - ZHOU Shan-shan; JIN Jing-peng; WANG Ji-qun; ZHANG Zhi-guo; FREEDMAN Jonathan H; ZHENG Yang; CAI Lu (Acta Pharmacologica Sinica, 2018)
Cardiovascular diseases (CVD) are the leading cause of morbidity and mortality in the world. Although considerable progress has been made in the diagnosis, treatment and prognosis of CVD, there is still a critical need for novel diagnostic biomarkers and new therapeutic interventions to decrease the incidence of this disease. Recently, there is increasing evidence that circulating miRNAs (miRNAs), i.e. endogenous, stable, single-stranded, short, non-coding RNAs, can be used as diagnostic biomarkers for CVD. Furthermore, miRNAs represent potential novel therapeutic targets for several cardiovascular disorders. In this review we provides an overview of the effects of several CVD; including heart failure, acute myocardial infarction, arrhythmias and pulmonary hypertension; on levels of circulating miRNAs. In addition, the use of miRNA as therapeutic targets is also discussed, as well as challenges and recommendations in their use in the diagnosis of CVD.